CARTR Plus: the creation of an ART registry in Canada. Issue 3 (6th June 2020) - Lanes, A; Fell, DB; Teitelbaum, M; Sprague, AE; Johnson, M; Wang, H; Elliott, M; Guo, Y; Meng, L; Yuzpe, A; Bissonnette, F; Leveille, MC; et al.
Abstract: STUDY QUESTION: What is the status of fertility treatment and birth outcomes documented over the first 6 years of the Canadian Assisted Reproductive Technologies Register (CARTR) Plus registry? SUMMARY ANSWER: The CARTR Plus registry is a robust database containing comprehensive Canadian fertility treatment data to assist with providing evidence-based rationale for clinical practice change. WHAT IS KNOWN ALREADY: The rate of infertility is increasing globally and having data on fertility treatment cycles and outcomes at a population level is important for accurately documenting and effecting changes in clinical practice. STUDY DESIGN, SIZE, DURATION: This is a descriptive manuscript of 183 739 fertility treatment cycles from 36 Canadian clinics over 6 years from the CARTR Plus registry. PARTICIPANTS/MATERIALS, SETTING, METHODS: Canadian ART treatment cycles from 2013 through 2018 were included. This manuscript described trends in type of fertility treatment cycles, pregnancy rates, multiple pregnancy rates, primary transfer rates and birth outcomes. MAIN RESULTS AND THE ROLE OF CHANCE: Over the 6 years of the CARTR Plus registry, the number of treatment cycles performed ranged from less than 200 to greater than 1000 per clinic. Patient age and the underlying cause of infertility were two of the most variable characteristics across clinics. Similar clinical pregnancy rates were found among IVF and frozen embryo transfer (FET) cycles with own oocytes (38.9 and 39.7% per embryo transfer cycle, respectively). Fertility treatment cycles that used donor oocytes had a higher clinical pregnancy rate among IVF cycles compared with FET cycles (54.9 and 39.8% per embryo transfer cycle, respectively). The multiple pregnancy rate was 7.4% per ongoing clinical pregnancy in 2018, which reflected a decreasing trend across the study period. Between 2013 and 2017, there were 31 811 pregnancies that had live births from all ART treatment cycles, which corresponded to a live birth rate of 21.4% per cycle start and 89.1% of these pregnancies were singleton live births. The low multiple pregnancy rate and high singleton birth rate are associated with the increase in single embryo transfers. LIMITATIONS, REASONS FOR CAUTION: There is potential for misclassification of data, which is present in all administrative health databases. WIDER IMPLICATIONS OF THE FINDINGS: The CARTR Plus registry is a robust resource for ART data in Canada. It provides easily accessible aggregated data for Canadian fertility clinics, and it contains data that are internationally comparable. STUDY FUNDING/COMPETING INTEREST(S): There was no funding provided for this study. The authors have no competing interests to declare.